Prospects for Reforming Federal Pay - Smith, Sharon P. (American Economic Review, 2016)
Twenty years have passed since President Kennedy declared that action was needed to assure that pay rates be comparable with private enterprise rates for the same level of work. Because there are no profit considerations in government and powerful political influences affect all decisions, special guidelines are needed for wage determination. During the subsequent years, the doctrine became the guiding principle in federal pay policy for both bluecollar and white-collar workers. Over time, however, the implementation of full comparability adjustments have more often been downgraded to satisfy other national policy goals. A major reform bill is now under consideration in Congress. Therefore, it is appropriate at this time to examine where we are in terms of achieving and maintaining and consider the prospects for reform.